Belief dynamics and explanations in ansprolog - Simari, Gerardo I. (2003)
Knowledge representation models are very important in the design of intelligent agents because they provide with mechanisms to manage beliefs and their dynamics. In this paper, we propose the use of AnsProlog* as a knowledge representation language, and develop a Non Prioritized Belief Revision operator based on the Answer Set semantics and the use of explanations. This operator is suitable for multiagent environments, in which agents can exchange information by having dialogues which explain their respective beliefs. A simple, yet complete example follows the presentation of this operator.